2016
DOI: 10.21037/jgo.2016.09.13
|View full text |Cite
|
Sign up to set email alerts
|

Impressive response to dual BRAF and MEK inhibition in patients with BRAF mutant intrahepatic cholangiocarcinoma—2 case reports and a brief review

Abstract: Intrahepatic cholangiocarcinoma (ICC) typically presents at an advanced stage and is associated with a poor oncological outcome. The median survival for metastatic ICC is less than 1 year with standard chemotherapy. ICC is associated with distinct oncogenic drivers including IDH (isocitrate dehydrogenase), HER-2 (human epidermal growth factor 2), and BRAF (v-Raf murine sarcoma viral oncogene homolog B), which may benefit from matching targeted therapies. Hereby we report 2 cases of BRAF V600E refractory ICC tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 11 publications
1
36
0
5
Order By: Relevance
“…However, these observations are promising, larger cohort studies are needed to further validate the findings. Tumor responses were also evaluated according to RECIST1.1 and a response rate of 50% was achieved across tumor types with median PFS and OS of 4.5 and 15 months, respectively, which are comparable with previous studies [ 13 , 28 , 29 ]. Interestingly, we observed a partial tumor response in both patients with NSCLC and a prolonged PFS and OS compared to previously reported (median PFS 9.7 months) [ 30 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, these observations are promising, larger cohort studies are needed to further validate the findings. Tumor responses were also evaluated according to RECIST1.1 and a response rate of 50% was achieved across tumor types with median PFS and OS of 4.5 and 15 months, respectively, which are comparable with previous studies [ 13 , 28 , 29 ]. Interestingly, we observed a partial tumor response in both patients with NSCLC and a prolonged PFS and OS compared to previously reported (median PFS 9.7 months) [ 30 ].…”
Section: Discussionsupporting
confidence: 84%
“…So far, the US Food and Drug Administration (FDA) approved the use of BRAF and MEK inhibitors for patients with BRAF‐mutated metastatic melanoma . However, recent studies provide encouraging data supporting the efficacy of BRAF and MEK directed therapeutic approaches in a large variety of BRAF mutated malignant diseases, including hairy cell leukemia, papillary thyroid carcinoma, intrahepatic cholangiocarcinoma and non‐small cell lung carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…The dual inhibition of BRAF and MEK is an alternative and potentially more efficient strategy to target the RAS-ERK pathway. In two independent reports, the combination of Dabrafenib and Trametinib showed durable clinical responses [55,56]. Finally, the preliminary results of a basket trial involving patients with BRAF mutation showed, in a cohort of pretreated biliary tract cancer, a response rate of 42% with a median overall survival of 11.7 months [57].…”
Section: Mapk (Mitogen-activated Protein Kinases) Pathwaymentioning
confidence: 95%